ANALISIS YURIDIS PERAN PENGADILAN DALAM UPAYA MEMBERIKAN LAYANAN BANTUAN HUKUM TERHADAP ORANG MISKIN MENURUT UNDANG-UNDANG NOMOR 16 TAHUN 2011 TENTANG BANTUAN HUKUM - M. Rizqi Darmawan; Triono Eddy (JURNAL DOKTRIN REVIEW, 2022)
The State of Indonesia is a state of law, which means that all forms of problems concerning matters between citizens and citizens or citizens and the state (government), must be based on the laws and regulations in force in Indonesia. As a consequence, every citizen is also entitled to the same legal protection without exception. So the State understands this problem with the issuance of Law Number 16 of 2011 concerning Legal Aid as a real action in protecting the equality of its citizens before the law. The problems raised are the role and process of courts in providing legal aid to the poor, legal consequences for legal aid institutions that do not provide legal aid for the poor, and efforts by law enforcement agencies to provide legal assistance to the poor. The role and process of the court in providing legal aid to the poor who provide legal assistance to the accused or suspect still has the same position in the eyes of the law in accordance with the values of Pancasila which is socially just and does not discriminate, especially for economic differences. The legal consequences for legal aid institutions that do not provide legal aid for the poor will be sanctioned in accordance with the provisions of the applicable law, the Government through the ministry of law and human rights revokes funds for legal aid services for the poor (izim OBH). The efforts of the legal apparatus in providing legal assistance to the poor, namely the court guarantees that the suspect or defendant is accompanied by legal counsel in accordance with Law 16 of 2011 concerning Legal Aid.